ON LEBESGUE CONSTANTS OF VILENKIN SYSTEMS - Sargsyan, S.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In the paper some properties of Lebesgue constants {L_n(W)}_n=1^∞ of Vilenkin system are investigated. Non almost convergence property for the sequence {L_n(W)_2 n}_n=2^∞ is obtained.